A rehabilitation ward in a district general hospital: first three years' experience. Issue 6658 (12th November 1988) - Walsh, K. J.; Barnes, M. P.; McLellan, D. L.
Abstract : The experience of the first three years' work on a ward for the rehabilitation of patients was reviewed. Adults with physical disabilities or mixed physical and psychological disabilities, including unstable or deteriorating conditions, were accepted for intensive rehabilitation. Most patients had neurological disorders. The ward policy was that each patient had considerable time with the therapist, maximum personal independence was encouraged, and multidisciplinary staff meetings were held to agree the goals of treatment. Much effort was spent helping patients and relatives to adapt to conditions of progressive disability, but the response to questionnaires suggested that these patients as well as those who did improve received some benefit from being on the ward. Overall the benefits of the intensive rehabilitation that was offered on this ward outweighed those from short stays on medical wards.